2020
DOI: 10.14202/vetworld.2020.1982-1987
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, absence of a bull and endoparasitic nematodiosis in beef cattle farms in an upland area of East Java, Indonesia

Abstract: Background and Aim: Cattle are an important economic asset for the rural community in East Java Province, Indonesia. The study aimed to provide updated data of cattle farm demography, productivity, as well as the role of the absence of a bull and nematodiosis in reduced productivity of beef cattle in an upland rural area of the province. Materials and Methods: The study was conducted in Sukowono village, Bondowoso region. A Census survey was conducted to collect data through interviews with farmers. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Moreover, training of BCS and the importance of supplementation to maintain BCS primarily at the beginning of the breeding season to support pregnancy requirements and post-calving for support of estrus is encouraged [ 55 ]. These interventions may not only assist beef cattle smallholders in SA but other tropical countries such as Somalia, Vietnam, and Indonesia reporting similar results [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, training of BCS and the importance of supplementation to maintain BCS primarily at the beginning of the breeding season to support pregnancy requirements and post-calving for support of estrus is encouraged [ 55 ]. These interventions may not only assist beef cattle smallholders in SA but other tropical countries such as Somalia, Vietnam, and Indonesia reporting similar results [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exotic breeds include Ongole, Brahman, Brahman cross, Angus, Simmental, Limousine and Australian Commercial Cross [53]. The average small beef farm in Indonesia has 2.4 cattle, with the average size of household farms in East and Central Java being less than two animals [38,54,55], but, in Nusa Tenggara Barat, Nusa Tenggara Timur, Sulawesi, Maluku and Papua, the average size is more than three cattle [38]. As many as 76.2% of household farmers are breeders and mature female cattle comprise 45.7% of the total cattle population [38].…”
Section: Beef Cattle Industrymentioning
confidence: 99%
“…As many as 76.2% of household farmers are breeders and mature female cattle comprise 45.7% of the total cattle population [38]. A village-level census in East Java reported that small-scale farms rely on artificial insemination for cattle breeding due to the lack of bulls, with the pregnancy rate reported to be just 26.8% [54]. As a result of low pregnancy and calving rates, domestic production can only satisfy 45% of the Indonesian demand for beef, and imports are needed to meet market demand [37].…”
Section: Beef Cattle Industrymentioning
confidence: 99%
See 1 more Smart Citation